Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.bej.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Agitation conditions for the culture and detachment of hMSCs from microcarriers in multiple bioreactor platforms

Abstract: Please cite this article in press as: A.W. Nienow, et al., Agitation conditions for the culture and detachment of hMSCs from microcarriers in multiple bioreactor platforms, Biochem. Eng. J. (2015), http://dx.a b s t r a c t In our recent work in different bioreactors up to 2.5 L in scale, we have successfully cultured hMSCs using the minimum agitator speed required for complete microcarrier suspension, N JS. In addition, we also reported a scaleable protocol for the detachment from microcarriers in spinner fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 17 publications
5
76
0
1
Order By: Relevance
“…Briefly, the harvesting procedure involved a two‐step process: (1) detachment of the cells from the microcarriers using an increased agitation rate of 150 rpm for 7 min during enzymatic reagent exposure and (2) separation of the cells and microcarriers prior to cell concentration by filtration. After detachment and separation, >95% cells with >95% viability were recovered (Nienow et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the harvesting procedure involved a two‐step process: (1) detachment of the cells from the microcarriers using an increased agitation rate of 150 rpm for 7 min during enzymatic reagent exposure and (2) separation of the cells and microcarriers prior to cell concentration by filtration. After detachment and separation, >95% cells with >95% viability were recovered (Nienow et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these challenges, clinical research and commercial groups have used the use of rocking motion bioreactor systems (e.g., GE Healthcare's WAVE bioreactor or BIOSTAT RM from Sartorius Stedim Biotech), which improve the homogeneity of the culture, sampling and implementation of process control strategies (Marsh et al, 2017;Vormittag et al, 2018). However, there have been extensive studies in the literature which have demonstrated the potential to culture numerous mammalian and human cells under both transitional and turbulent fluid dynamic conditions for both free suspension cells (Nienow, 2006) and adherent cells on microcarriers (Chen, Chew, Tan, Reuveny, & Weng Oh, 2015;Nienow et al, 2016;Rafiq et al, 2017). Some early work was successful in demonstrating the growth of T-cells in both spinner flasks and small bioreactors (Bohnenkamp, Hilbert, & Noll, 2002;Carswell & Papoutsakis, 2000) but neither used Dynabeads for cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…enzymes, chelators), magnetic or even stimuli‐responsive (e.g. thermo‐responsive, pH‐responsive, electro‐responsive, photo‐responsive).…”
Section: Introductionmentioning
confidence: 99%